PENGARUH SOFTWARE CABRI 3D TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMA PEKANBARU - Putri Wahyuni; Andini Dwi Rachmawati (Journal on Mathematics Education Research (J-MER), 2022)
This study aims to see the effect of the Cabri 3d software on the mathematical critical thinking skills of SMA PGRI students in Pekanbaru in the 2021/2022 academic year on the material of the position of the line and the plane. This research is a quantitative study with a quasi-experimental method (quasi-experimental), with the population in this study being all students of class XII IPA PGRI PEKANBARU. The sample used is a saturated sample where class XII IPA 1 and XII IPA 2 are the research samples, which means that the entire population is the sample. The research design used was The Nonequivalent Post-Test Only Control Group Design. The data analysis technique used for the hypothesis is using the Mann Whitney u test with the results obtained a sig value of 0.00 0.05, so it can be concluded that there is an effect of Cabri 3d software on students' mathematical critical thinking skills. Keywords: Cabri 3d software, mathematical critical thinking skills, Geometry